Information en temps réel et optimisation du déplacement - François Adoue (Netcom)
Some applications available on smartphones are designed to facilitate trips on public transportation networks by giving personalized, real-time and useful information to travellers and commuters. This research is based on twenty semi-structured interviews of daily users of public transportation in the Paris region. It aims to provide a better understanding of the determinants of the use of real-time information through smartphones. One can distinguish two motivations for the use of applications: helping the user to plan a trip or, on the contrary, helping the user to adapt to the spatial and temporal constraints of the trip.